Modernization of the methodology for obtaining phase transition temperatures using the piezoresponse force microscopy exemplified by study of a phase transition in the PZT single crystal - Vakulenko Aleksandr; Vanina Polina; Filimonov Alexey; Vakhrushev Sergey (St. Petersburg Polytechnical University Journal: Physics and Mathematics)
A chopper amplification technique has been developed to correct zero drift when measuring the magnitude of the piezoelectric response using the PFM method under conditions of continuous temperature change. Employing this technique, the temperatures of the antiferroelectric – ferroelectric phase transition of a PZT 4% single crystal were obtained. A qualitative agreement with the results of measuring the saturation polarization obtained by the Sawyer – Tower method makes it possible to assert that the technical assumptions made are quite reasonable and the developed method is worthy of widespread use in such measurements.